(untitled) (Diametros, 2016)
The article deals with the question of the value of the history of philosophy for philosophical research. In the first part, it proposes a classification of possible functions realized by references to the philosophical tradition in a philosophical treatise. The proposed typology is meant as a practical tool for identifying and comparing the usage of the past in philosophical texts of any historical period. The second part of the paper illustrates how the classification can be employed by applying it to determine the functions of Aristotle’s discussions of the pre-Socratic doctrines in Metaphysics A.